Application of Genetic Engineering for Control of Bacterial Wilt Disease of Enset, Ethiopia’s Sustainability Crop - Merga, Ibsa Fite; Tripathi, Leena; Hvoslef-Eide, Anne Kathrine; Gebre, Endale (Frontiers in Plant Science, 2019)
Enset (Ensete ventricosum (Welw.) Cheesman) is one of Ethiopia’s indigenous sustainability crop supporting the livelihoods of about 20 million people, mainly in the densely populated South and Southwestern parts of the country. Enset serves as a food security crop for humans, animal feed and source of fiber for the producers. The production of enset has been constrained by plant pests, diseases and abiotic factors. Among these constraints, bacterial wilt disease has been the most important limiting factor for enset production since its outbreak five decades ago. There is no known bacterial wilt disease resistant genetic material in the enset genetic pool to transfer this trait to susceptible enset varieties through conventional breeding. Moreover, the absence of effective chemicals against the disease has left farmers without means to combat bacterial wilt for decades. Genetic engineering has been the alternative approach to develop disease resistant plant materials in other crops where other breeding tools are ineffective. This review discusses enset cultivation and recent developments addressing the control of bacterial wilt disease in enset and related crops like banana to help design effective strategies.